Photocatalysis degradation TNR in TiO2 suspension. - Chất, Nguyễn Văn; Khuê, Đỗ Ngọc; Đạt, Nguyễn Văn (Vietnam Journal of Chemistry, 2012)
The photocatalytic degradation of TNR in a circular photocatalytic reactor, using a UV lamp as a light source and TiO2 as a photocatalyst, was investigated. The effects of various parameters such as the initial TNR concentration, and the initial pH on the TNR degradation rate of TiO2 photocatalysis were examined. In the presence of both UV light illumination and TiO2 catalyst, TNR was more effectively degraded than with either UV or TiO2 alone. The reaction rate was found to obey pseudo first-order kinetics represented by the Langmuir–Hinshelwood model. In the mineralization study, TNR (30 mg/l) photocatalytic degradation resulted in an approximately 79% TOC decrease after 60 min, and were further degraded. NO3-, NO2-, and NH+4 were detected as the nitrogen byproducts from photocatalysis and photolysis, and more than 50% of the total nitrogen was converted mainly to NO3- in the photocatalysis. However, NO3- did not adsorbed on the TiO2 surface. TNR showed higher photocatalytic degradation efficiency at neutral and acide pH.